Reversed phase liquid chromatographic conditions for simultaneous determination of antihypertensive formulations - Joshi, Shalini; Sharma, Amrita; Rawat, MS; Bal, CS (Asian Journal of Pharmaceutics (AJP), 2014)
Rapid and simple reversed phase chromatographic conditions have been developed to separate pharmacologically active components of antihypertensive drug formulations (enalapril maleate + amlodipine besilate and ramipril 1 hydrochlorothiazide) on high-performance liquid chromatography (HPLC) and thin layer chromatography. The mobile phase consists of methanol–water (60:40 v/v) for reversed-phase thin layer chromatography (RPTLC). Detection was carried out by iodine vapors. The HPLC method was developed on a C-18 column with detection carried out by a UV detector at 215 and 220 nm for enalapril maleate 1 amlodipine besilate and ramipril + hydrochlorothiazide, respectively. The HPLC method was validated using data elements specificity, linearity and range, and accuracy and precision.